Equal use of Indigenous and scientific knowledge in species assessments: A case study from the Northwest Territories, Canada. (May 2023) - Singer, Claire L.; Routh, Mélanie R.; Grabke, Michele J.; Andrew, Leon; Carrière, Suzanne; Guile, Aimee; Andre, Alestine; Thompson, Allison; Simmons, Deborah; Cooper, Kaytlin; Yonge, Lynda; Rabesca, Moise; et al.
Abstract: Interest in meaningfully including and applying Indigenous knowledge in species at risk assessment processes is growing, but serious procedural challenges remain to achieving this in international, national, and regional organizations responsible for assessments. Indigenous knowledge is grounded in place-based, spiritual knowledge and values passed down through generations. This system of knowledge is often misinterpreted, taken out of context, or pushed aside entirely when integrated into processes built for scientific knowledge. Recognizing these challenges, the Species at Risk Committee of the Northwest Territories, Canada, sought to create a process that would permit the meaningful consideration of both Indigenous and scientific knowledge systems in species at risk assessments. This resulted in the development of two sets of complementary assessment criteria with independent components reflecting Indigenous knowledge and scientific knowledge, respectively. The final status assessment is informed by both components, to the extent possible. The Indigenous knowledge criteria also permits a species to be assessed as at risk where Indigenous cultures or traditional ways of life are impeded or rendered impossible because of changes to a species or its habitat. This unique structure permits a more equitable consideration of all sources of best available knowledge and more effectively reflects biocultural linkages. The meaningful consideration of Indigenous knowledge in species at risk assessments is a topic of high importance and we encourage others to re-evaluate the ways in which species at risk assessments are completed. Highlights: Meaningful inclusion of Indigenous knowledge in decision-making remains scarce. Species assessments globally favour technical and quantitative scientific criteria. Northwest Territories offers a dual and complementary species assessment structure. Indigenous criteria reflect observations of change by knowledge holders. Consist of changes in abundance, habitat, movement, range, and exposure to threats.